Radical surgical approach to chronic suppurative osteomyelitis : case repor = Abordaje quirúrgico radical de una osteomielitis crónica supurativa : reporte de caso - Vargas Rojas, Diana Carolina
Diabetes mellitus is a systemic condition potentially related to an increased risk of progression of various infections such as chronic osteomyelitis by accelerating the inflammatory process with bone tissue necrosis and suppuration. Therefore, if there is no proper management of these infections, they can be life-threatening as they spread to deeper spaces in the head and neck. We describe the case of a 52-year-old male patient with a history of diabetes mellitus and grade III osteoarthritis who was diagnosed with chronic suppurative osteomyelitis of the mandible. He underwent a multidisciplinary surgical intervention in which he underwent a hemimandibulectomy with immediate mandibular reconstruction. The present case highlights the importance of early and radical treatment of patients with chronic suppurative osteomyelitis of the mandible and systemic comorbidities. In addition, this case presents a review of diabetes mellitus and the risk of developing odontogenic infections and complications when invading deeper spaces in the head and neck. Therefore, in this population, careful planning is required for early surgical and pharmacological treatment.